Hubungan Pengetahuan Dan Dukungan Suami Dengan Penggunaan Alat Kontrasepsi Di Wilayah Kerja Puskesmas Padang Tepong Kabupaten Empat Lawang - Saripudin Saripudin; Hasanudin Nuru; Epina Felizita (Jurnal Kebidanan Manna, 2022)
The family planning program is an attempt to measure the number and distance of children desired, to achieve this, several ways are made to prevent or delay pregnancy, although in practice quality family planning services have not fully reached the entire archipelago. The purpose of this study was to determine the relationship between knowledge and husband's support with the use of contraceptives in the Padang Tepong Public Health Center, Empat Lawang Regency. The method used is an analytic survey research with a cross sectional research design, the data is collected in the form of primary data by distributing questionnaires to family planning acceptors in the Padang Tepong Public Health Center, Empat Lawang Regency using a simple random sampling technique of 86 pregnant women. Data analysis was performed using the Chi-Square test. The results of the univariate analysis showed that almost half of the respondents had less knowledge, more than half of the respondents did not get husband's support and more than half of the respondents used hormonal contraception. The results of the bivariate analysis showed that there was a relationship between knowledge and the use of contraceptives (p=0.001) and there was a relationship between husband's support and the use of contraceptives (p=0.024). Researchers suggest to the puskesmas that the results of this study can be used as input to improve health services for family planning acceptors.